Senhora das Águas: Memórias da antiga Procissão de Navegantes do Porto de Pelotas - RS - Farinha, Alessandra Buriol (2012)
The main goal of this study is to recover the memories of the ancient Procession of Our Lady of Navigators which happens in the Port region in the city of Pelotas. Likewise, it seeks to elucidate how it was taken toforgetfulness. The Navigators Feast occurred in Pelotas for the first time in 1932, at the Port Neighborhood, organized by the Main Church Sacred Heart of Jesus,known as Port Church. The religious event involved land and water processionsthrough the main streets of the port neighborhood and through both São Gonçalo Channel and Pelotas Arroyo, respectively. For nearly four decades, the Navigators Feast occurred annually, with participation by clerical, civil and military authorities, thousands of faithful, religious associations, sponsors, musical bands, cultural attractions, food vendors and fireworks, among others. In the 1970s, the Procession moved to the Fishermen's Colony Z-3, about 25 km from the center of Pelotas.The displacement of the Image of the Saint from the Port district represented (especially for the devotees) the loss, the forgetfulness. The main methodological approachused to substantiate the memories of the old Navigators Feast was the oral history, with witnesses devotees of the Santa, old residents in the neighborhood, who used to participate in the Procession. Were also consulted primary sources, such as the First Tumble Book of the Port Parish (1912), as well as journals from 1932 to 1972. This study is contextualized by the history of the Port s Church and also by Pelotas Archdiocese, place of origin of devotion to Navigators, and the emergence of the Navigators Feast in town, idealized by Monsignor Luiz Gonzaga Chierichetti. It was possible to verify a unit in context of ethnic religious group involved in the feast. The devotees respondents share their memories about the Feast and feel sorry for its forgetfulness. According to the research, the procession is directly related to life, to work, to sociability and the territory of Port s district. It was discovered that most of the memories of the Navigators Feast at Port Neighborhood shows its happiest parts, which transforms the space into a "privileged place" emotionally charged of life, faith, work